A Lens to Understand Sanitation Workers and their Health Status in India - Kannolath, Rejesh Bose (Journal of Pharmacy Practice and Community Medicine)
It is estimated that there is around 5 million in India are employed as sanitation workers. Among them two millions are working under “High Risk” conditions. Despite of rapid growth in urbanisation and technology the working condition of these sanitation workers have remain unchanged since independence. Another inevitable concern needs to be understood while we study about sanitation workers is that it is also deeply rooted in Indian Caste system which assigns duties of sweeping, cleaning toilets, Manual scavenging to individuals from lowest sub castes of Dalit community. A sanitation worker's job is very much conceived as a job which falls under the lowest class of job when it comes to categorisation of jobs, but on reality check, it is understood that without them communities and societies can’t succeed and sustain. They forms the backbone of the civic cleaning system of any society and they performs valuable services to the society and state by collecting garbage and removing it to proper disposal areas.